Nalar Sufisme dalam Pengarustamaan Moderasi Beragama di Indonesia - Islamy, Athoillah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The mainstreaming of religious moderation in Indonesian is not welcomed positively by all elements of society. This is because there are some views that consider the mainstreaming of religious moderation as a form of liberalization or secularization of religion in state life. Through a normative-philosophical approach, this qualitative study aims to identify and explore the content of Sufism values on the four indicators of religious moderation formulated by the Ministry of Religious Affairs of the Republic of Indonesia. Data collection of this study through documentation. Data analysis includes the stages of reduction, presentation, and verification. The results of this study show the dimensions of Sufism values in indicators of religious moderation in Indonesia, including the value of mahabbah in indicators of tolerance and anti-radicalism, namely in the formation of Islamic religion full of compassion, love, and peace. Then, the value of itsar on the indicator of national commitment, namely in the formation of Islamic religion that maintains mutual benefit for the integration of social life. Furthermore, the value of futuwwah on indicators accommodating to local culture, namely in the formation of Islamic religion that is fair and non-discriminatory against cultural plurality. The theoretical implications of this study emphasize that there is a meeting point related to the manifestation of the value of Sufism teachings with indicators of religious moderation in Indonesia. The limitation of this study is that it has not examined the program of the Ministry of Religious Affairs of the Republic of Indonesia in socializing the integration of Sufism values with various indicators of religious moderation that it formulated.